Edukasi Pola Hidup Bersih dan Sehat pada remaja di Gereja HKBP Villa Duta Mas Bogor - Triyana Sari; Erick Sidharta; Sari Mariyati Dewi Nataprawira; Yovian Timothy Satyo; Fladys Jashinta Mashadi (PPNI UNIMMAN, 2023)
Clean and Healthy Lifestyle (PHBS) is one of the Ministry of Health's Community Movement (Germas) programs, where the community acts as an agent of change and improves the quality of daily behavior towards a clean and healthy life. The advantage of PHBS is that people are health aware and have the knowledge and awareness to live a clean and healthy lifestyle. As a public place, the church organizes various activities that many groups, from children to adults, can take part in. Apart from that, the church also plays a role in spiritual and physical education, meaning that children and teenagers not only gain spiritual knowledge, but also physical knowledge for everyday life. This activity aims to increase knowledge and awareness about clean and healthy living behavior from an early age.